Association Between Onset-to-Door Time and Clinical Outcomes After Ischemic Stroke. Issue 11 (November 2017) - Matsuo, Ryu; Yamaguchi, Yuko; Matsushita, Tomonaga; Hata, Jun; Kiyuna, Fumi; Fukuda, Kenji; Wakisaka, Yoshinobu; Kuroda, Junya; Ago, Tetsuro; Kitazono, Takanari; Kamouchi, Masahiro; Ishitsuka, Takao; et al.
Abstract : Background and Purpose—: The role of early hospital arrival in improving poststroke clinical outcomes in patients without reperfusion treatment remains unclear. This study aimed to determine whether early hospital arrival was associated with favorable outcomes in patients without reperfusion treatment or with minor stroke. Methods—: This multicenter, hospital-based study included 6780 consecutive patients (aged, 69.9±12.2 years; 63.9% men) with ischemic stroke who were prospectively registered in Fukuoka, Japan, between July 2007 and December 2014. Onset-to-door time was categorized as T 0-1, ⩽1 hour; T 1-2, >1 and ⩽2 hours; T 2-3, >2 and ⩽3 hours; T 3-6, >3 and ⩽6 hours; T 6-12, >6 and ⩽12 hours; T 12-24, >12 and ⩽24 hours; and T 24-, >24 hours. The main outcomes were neurological improvement (decrease in National Institutes of Health Stroke Scale score of ≥4 during hospitalization or 0 at discharge) and good functional outcome (3-month modified Rankin Scale score of 0–1). Associations between onset-to-door time and main outcomes were evaluated after adjusting for potential confounders using logistic regression analysis. Results—: Odds ratios (95% confidence intervals) increased significantly with shorter onset-to-door times within 6 hours, for both neurological improvement ( T 0- 1, 2.79 [2.28–3.42]; T 1-2, 2.49 [2.02–3.07]; T 2-3, 1.52 [1.21–1.92]; T 3-6, 1.72 [1.44–2.05], with reference to T 24- ) and good functional outcome ( T 0-1, 2.68 [2.05–3.49], T 1-2 2.10 [1.60–2.77], T 2-3 1.53 [1.15–2.03], T 3-6 1.31 [1.05–1.64], with reference to T 24- ), even after adjusting for potential confounding factors including reperfusion treatment and basal National Institutes of Health Stroke Scale. These associations were maintained in 6216 patients without reperfusion treatment and in 4793 patients with minor stroke (National Institutes of Health Stroke Scale ⩽4 on hospital arrival). Conclusions—: Early hospital arrival within 6 hours after stroke onset is associated with favorable outcomes after ischemic stroke, regardless of reperfusion treatment or stroke severity. Abstract : Supplemental Digital Content is available in the text.